THE EFFECT OF PRICE AND WORD OF MOUTH ON PURCHASING DECISIONS WITH BRAND IMAGE AS AN INTERVENING VARIABLE AT WARKOP AGAM STABAT - Fairuza Rikha Amri; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (PT. Radja Intercontinental Publishing, 2026)
This study investigates the effects of price and word of mouth (WOM) on purchasing decisions, with brand image acting as an intervening variable. Conducted at Warkop Agam Stabat, a local coffee shop in Stabat, Indonesia, the study uses a quantitative research method involving primary and secondary data collection from 216 respondents. The data analysis includes descriptive statistics and Structural Equation Modeling (SEM). The findings reveal that price negatively affects both purchasing decisions and brand image, while WOM positively influences brand image but does not directly affect purchasing decisions. However, brand image significantly influences purchasing decisions and mediates the relationships between price, WOM, and purchasing decisions. This study contributes to the understanding of consumer behavior in the context of small local businesses.